Use of a modified occupational therapy performance measure (mCOPM) for assistive technology outcomes in postsecondary education - Pinkelman, Ashley, author; Green, David, advisor; Roll, Marla, committee member; McClure, Merinda, committee member (Colorado State University. Libraries, 2015)
It is widely agreed upon that there are functional benefits in the use of assistive technology for individuals with disabilities (Fuhrer, 2001). However, clinicians and researchers have struggled to adopt a unified practice to measure outcomes of intervention (Arthanat, Simmons, & Favreau, 2012; DeRuyter, 1996; Scherer, 1996). This challenge grows especially difficult when looking outside of the major rehabilitation sector to other settings such as education. Assistive technology can be unique in its focus of intervention, accessibility of services, and clientele. According to Section 504 in the Rehabilitation Act of 1973, post-secondary schools must provide means to accommodate students to participate in education including using assistive technology to meet this goal. However, there currently is no assessment measure for assistive technology that considers the unique factors of a post-secondary education setting. The Canadian Occupational Performance Measure (COPM) (Law et al., 2000) has been used to assess the effectiveness of assistive technology. However, modification of the areas of occupation in the COPM is necessary to better reflect areas addressed by assistive technology in a postsecondary education setting. The major finding of this research project is that a modified version of the COPM is a sensitive and useful measure of performance and satisfaction utilizing assistive technology services in a postsecondary education setting.
Keywords: Canadian occupational performance measure; modified Canadian occupational performance measure; postsecondary education; disability; assistive technology; outcome measure